Analysis and design of a MEMS DC/DC converter. Issue 3 (12th February 2015) - Qu, Furong; Nie, Mengyan; Liu, Yu; Ou, Yi
<x xml:space="preserve">Abstract</x> This paper presents the analysis and simulation of a microelectromechanical system (MEMS) DC/DC converter based on vibration‐to‐electric energy conversion. The device transfers and accumulates the mechanical energy from ambient vibration via a variable capacitor. After the key parameters of the device are carefully discussed, the dynamics analysis is given based on the differential equation of the system. The approach provided in this paper is very helpful in designing and essentially understanding the MEMS DC/DC converter with high performance. © 2014 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.